Article Commentary: Clinical Severity Measures for Psoriasis: A Case for the PASI. Issue 2 (March 2016) - Beroukhim, Kourosh; Farahnik, Benjamin; Danesh, Melissa; Nguyen, Catherine; Koo, John; Levin, Ethan
The Psoriasis Area and Severity Index (PASI) and Physician Global Assessment (PGA) are the most commonly used tools for the evaluation of psoriasis disease severity in clinical trials. Based on U.S. Food and Drug Administration requirements, many recent trials concerning measurement of psoriasis disease severity have included the PGA as a primary endpoint alongside the PASI. In this commentary, we review the advantages and disadvantages of the PASI and PGA scales, and discuss an example of a psoriasis patient in whom PGA fails to capture clinically significant disease improvement. We argue that despite its limitations, the PASI is a more accurate and descriptive instrument than the PGA for the assessment of psoriasis severity.